Pengaruh Serbuk Cangkang Keong Sawah Sebagai Pengganti Sebagian Semen Pada Beton Normal - Reiner Putra Pakanan; Jonie Tanijaya; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2021)
Along with the increasing pace of development, many methods and research have been carried out and developed aimed at increasing the strength of concrete, one of which is by utilizing waste rice snail shells as a partial replacement of cement. This snail is considered a pest for farmers. Snail carcasses can also damage the environment and cause a bad smell. This can be used and utilized as an alternative material in concrete mixtures. The percentage of use of rice snail shell substitution varied, namely 0%, 10%, and 15%. The tests carried out were the compressive strength test, split tensile strength test, flexural strength test, and the modulus of elasticity of concrete with a concrete quality of 25 MPa. The test objects used were cylinders measuring 15 cm and 30 cm high and beams measuring 60 cm × 15 cm × 15 cm with variations in age of 7 days, 21 days, and 28 days. The highest value was obtained at 10% snail shell variation with 27,540 MPa, 2,735 MPa, 4,131 MPa, respectively. so that the 10% snail shell variation used in this study is still safe to use as a cement substitution material in normal concrete mixtures.